In vitro and in-vivo exploration of physostigmine analogues to understand the mechanistic crosstalk between Klotho and targets for epilepsy - Dahalia, Mansi; Majid, Haya; Khan, Mohd Junaid; Rathi, Akshat; Khan, Mohd Ashif; Khan, Imran Ahmd; Samim, Mohammed; Rehman, Sayeed Ur; Noorani, Md Salik; Vohora, Divya; Nidhi, (Frontiers in Pharmacology, 2025)
BackgroundEpilepsy and seizures are characterized by neuronal hyperexcitability and damage, influenced by metabolic dysregulation, neuroinflammation, and oxidative stress. Despite available treatments, many patients remain resistant to therapy, necessitating novel therapeutic strategies. Klotho, a neuroprotective, anti-inflammatory, and antioxidative protein has emerged as a potential modulator of epilepsy-related pathways.ObjectiveThis study investigates the therapeutic potential of novel physostigmine analogues in regulating Klotho expression and its downstream targets in epilepsy.MethodsAn integrative in vitro and in vivo approach was employed in PTZ-induced kindled mice. Behavioral assessments, including the Morris Water Maze (MWM), Rota Rod, Black and White Box, and Tail Suspension tests were conducted. Biochemical analyses quantified serum glucose, lipid profiles, pro-inflammatory cytokines (TNF-α, FOXO1), and apoptotic proteins (caspase-3). Quantitative real-time PCR (qRT-PCR) was performed to assess Klotho and epilepsy-associated gene expression (STAT3, Bax, Bcl2).ResultsThe synthesized physostigmine analogues exhibited varying inhibitory effects on Klotho transcriptional activators, with Compound C (1,8-bis(phenylsulfonyl)-1,8-dihydropyrrolo [2,3-b] indole) showing the weakest inhibition (IC50 = 1.31 µM). In vivo, Compound C demonstrated anticonvulsant (p < 0.05), neuroprotective (5 mg/kg, p < 0.05, 10 mg/kg, p < 0.01, 20 mg/kg p < 0.0001), antidepressant (p < 0.05), and anti-inflammatory (p < 0.05) effects in PTZ-induced seizure models, improving motor function (p < 0.001), cognitive performance (p < 0.01), and reducing neuroinflammatory/metabolic markers (p < 0.05), while modulating STAT3 (p < 0.001), BAX (p < 0.001), Bcl2 (p < 0.05), and Klotho (p < 0.05) gene expression.ConclusionThe therapeutic potential of 1,8-bis(phenylsulfonyl)-1,8-dihydropyrrolo [2,3-b] indole in epilepsy via Klotho modulation was observed. Targeting metabolic, inflammatory, and apoptotic pathways presents a promising strategy for epilepsy management. Further research is required to optimize clinical translation and ensure long-term efficacy and safety.